ALTERNATIVES AND HAZARDS OF FISCAL CONSOLIDATION IN SERBIA - Madžar, Ljubomir (International Journal of Economic Practice and Policy, 2014)
Serbia is facing a serious fiscal crisis which could easily result in what is euphemistically called the crisis of public indebtedness, but which is just less shocking term for the bankruptcy of the state. The share of the budgetary deficit in the GDP is hovering in the hazardous neighborhood of 6 percent, while the ratio of the public debt to the GDP is about to surpass equally perilous limit of 60 percent. The legally prescribed limits for these indicators are 4.5 and 45 percent. As these limits are formalized by still valid and obliging laws, one is bound to conclude that Serbia is not only trapped into a precarious economic situation but also has seriously violated and in fact damaged her own legal order, opening the door for unforeseeable and numerous further disturbances with far-reaching consequences. In view of the precarious overall economic situation the diagnosis of the economy can be quite brief: slowing down of economic growth with recently recorded negative rates, unprecedented unemployment, massive balance of payment deficit and inflation still the highest in the region and among the highest in Europe. Unsustainable fiscal deficit and threatening – and still rapidly growing – public and private indebtedness are additional features which complete this gloomy picture. In examining determinants and possible causes of the economic collapse a general feature of the economy and the society at large is singled out. It consists in the habit, which turned into a true tradition, of living far above own available means: starting with termination of the II World War, society has been exposed to variously generated inflows of supplementary foreign resources which enormously raised spending habits and made the system unable to reduce consumption and adjust to new circumstances once the inflow faded out or threatened to disappear altogether. A particular form of hysteresis developed and reduced the saving potential of the economy undercutting permanently its growth prospects. A host of other, as it were derived factors developed against this general prospect: overvaluation of the currency greatly reducing the competitiveness of the economy, fragile accommodation to the external sources of investment finance without prospects of stable and lasting inflows, structural deformations of the economy with oversized service sector leading to what is called virtualization of the growth and, above all and as a result of all of these, to the unsustainability of the present development scenario. Unsustainable development trajectory cannot fail to produce a crisis of foreign debt, grave imbalances in external economic relations and permanent disequilibria in public finance with revenues lastingly falling short of expenditures. In view of a high likelihood of the breakdown of the system, the authorities were forced to formulate and start to implement a consolidation program of high urgency. But they are confronted with many formidable constraints. On the expenditure side there are many extremely rigid components fixed by law, whereby the authorities are confronted with equally restraining political hurdles: cutting expenditure is overly costly in political terms. On the tax side, there are grave limits to what financially exhausted economy and the populace could additionally bear and the danger of further decelerating the worn out economy. Reduction of the budget deficit is categorically needed and the set of measures designed by the government in order to achieve that goal is briefly analyzed. It is found out that, out of the uncompromisingly needed reduction of the budget deficit by 2 percent, only 1 percent can be produced by the proposed program with reasonable certainty, with the end result turning out insufficient and falling far away from what is unconditionally needed.
Keywords: hypertrophied consumption; macroeconomic imbalances; balance of payment deficit; taxation; public revenues; budgetary deficit; public debt; economic policies; political constraints on policy measures; unsustainability of growth